LncRNA ZFAS1 promotes the transformation from prostatitis to prostate cancer via myddosome assembly-mediated activation of NF-κB signaling - Tao Feng; Hao Shen; Shenglan Ye (Discover Oncology)
Abstract Background Prostatitis is a critical factor in promoting carcinogenesis, but the key molecular mechanisms remain unknown. Long noncoding RNA (lncRNA) ZFAS1 was reported to be involved in the development of human cancers including prostate cancer and some inflammatory diseases. This research aims at investigating the function of ZFAS1 in regulating prostatitis to prostate cancer transformation and the underlying mechanism. Methods A prostatitis-cancer transformation cell model RWPE-1/THP-1 was established by co-culturing human prostate epithelial cells RWPE-1 with human acute monocytic leukemia cells THP-1. CCK-8, colony formation, and flow cytometry assays were used to detect the effects of ZFAS1 knockdown or overexpression on the proliferation and apoptosis and malignant transformation ability of the model cells. The influence of ZFAS1 knockdown on the levels of apoptosis-related proteins, MyD88 protein aggregation in cell lysate and pellet fractions, and the phosphorylation of IKKβ, IκBα, and NF-κB p65 in RWPE-1/THP-1 cells. Immunofluorescence staining was used to detect NF-κB p65 nuclear translocation in RWPE-1/THP-1 cells. ST2825 was used to further confirm whether ZFAS1 affects prostatitis to prostate cancer transformation by regulating NF-κB pathway through modulating MYD88 dimerization and the subsequent myddosome assembly. Results ZFAS1 expression was markedly increased in RWPE-1/THP-1 cells. ZFAS1 silencing repressed the proliferation and facilitated the apoptosis of RWPE-1/THP-1 cells. P-IKKβ, p-IκBα and p-p65 protein levels and NF-κB p65 nuclear translocation were significantly enhanced in RWPE-1/THP-1 cells, which were reversed by ZFAS1 knockdown. ZFAS1 knockdown exerted the same inhibitory effects as ST2825 treatment on the degree of MyD88 aggregation and NF-κB pathway activation in RWPE-1/THP-1 cells, suggesting that ZFAS1 knockdown inactivated the NF-κB pathway in RWPE-1/THP-1 cells through suppressing MYD88 dimerization and the subsequent myddosome assembly. In addition, ST2825 treatment overturned the influence of ZFAS1 overexpression on the proliferation and apoptosis of RWPE-1/THP-1 cells. Conclusion ZFAS1 promotes prostatitis to cancer transformation by activating the NF-κB signaling through promoting MYD88 dimerization and the subsequent myddosome assembly.